A green, effective, and synergistic flame retardant for poly(ethylene-co-vinyl acetate) resin. (December 2022) - Liu, Qi; Feng, Dong; Zhao, Wenbo; Xie, Delong; Mei, Yi
Highlights: A novel phosphaphenanthrene/black phosphorene (DBP) hybrid composite is proposed as high efficient flame-retardant for EVA. The DBP system can achieve a Si-P molecule-scale dispersion in EVA matrix by a hydrogen bond complexation. DBP can significantly improve the thermal stability and flame resistance of EVA host without sacrificing its mechanical properties. Abstract: It is a challenge to prepare flame-retardant composites via addition of low content of fire retardant all the time. In this contribution, a compounding method based on combining long-chain phosphaphenanthrene (DPP) flame retardant and two dimensional (2D) black phosphorene (BP) is used to achieve molecule-scale dispersion of a Si-P flame retardant in poly(ethylene-co-vinyl acetate) (EVA) matrix (donated as EVA/DBP) by the interaction of intermolecular hydrogen bonds. By this way of doing, EVA/DBP composites with various flame retardant contents were investigated. Cone calorimeter, vertical combustion, thermo-gravimetric analysis, scanning electron microscope, Raman Spectrum, and Fourier transform infrared spectroscopy are used to evaluate the flame retardance and analyze the corresponding mechanisms. The results show that the DBP can effectively improve the flame retardant properties and thermal stability of EVA with slight influence on its mechanical performance. Compared with pure EVA resin, EVA/DBP composite with 5 wt% dosage of DBP achieves UL94-V0 rating, 9.6% increased in limiting oxygen index (LOI), 16.1% and 47.5% reduction in total heat release (THR) and peak heat release rate (PHRR), respectively. Moreover, the tensile yield stress and elongation at break are only reduced by 8.1% and 6.2%, respectively. It shows that the interaction between DBP and EVA effectively promote gas phase fire resistance.